FPR2: A Novel Promising Target for the Treatment of Influenza - Alessi, Marie-Christine; Cenac, Nicolas; Si-Tahar, Mustapha; Riteau, Béatrice (Frontiers in Microbiology, 2017)
The Formyl-peptide receptor-2 (FPR2) is a seven transmembrane G protein-coupled receptor, which plays an important role in sensing of bacteria and modulation of immune responses. FPR2 is also used by viruses for their own profit. Annexin A1, one of the multiple ligands of FPR2, is incorporated in the budding virus membrane of influenza A viruses (IAV). Thereby, once IAV infect a host cell, FPR2 is activated. FPR2-signaling leads to an increase in viral replication, a dysregulation of the host immune response and a severe disease. Conversely, experiments using FPR2 antagonists in a preclinical model of IAV infections in mice showed that blocking FPR2 protects animals from lethal infections. Thus, FPR2 represents a very attractive host target against influenza. In this review we will give an overview on the pathogenesis of influenza with a focus on the role of FPR2 and we will discuss the advantages of using FPR2 antagonists to treat the flu.